Controlling the properties of 3D-printed sodium caseinate emulsion gels by tuning starch-induced network architecture - Kangning Zhang; Fangyuan Tian; Xiaojing Li; Shengju Ge; Yanping Wang; Yang Qin; Man Li; Rongbo Fan; Qingjie Sun; Na Ji (Food Research International, 2026)

Inhibition of digestive enzymes with EGCG-loaded inverse alginate beads: a strategy for modulating starch digestion - Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Meng Li; Yang Qin; Man Li; Qingjie Sun; Jian He; Na Ji (Food Chemistry, 2026)

Zein-calcium alginate dual-shell liquid-core beads for tailored starch digestibility: Structural design, functional performance, and mechanistic analysis - Yang Qin; Xiya Zhang; Jinling Zou; Shengju Ge; Xiaojing Li; Man Li; Qingjie Sun; Qingze Han; Huanying Qin; Jian He; Na Ji (Food Chemistry, 2026)

Quercetin exerts radioprotective effects against radiation-induced intestinal injury with involvement of the PI3K-AKT/Caspase-3 axis - Qing Guo; Zhibing Tang; Zhenyu Hou; Ge Yan; Jiaxuan Wang; Man Zhang; Ruige Ma; Juan Wang; Qiong Feng; Zhen Wang; Chunlei Wang; Lin Zhao (Molecular and Cellular Biochemistry, 2026)

Microstructural development leading to rheological transition of granular suspensions - Zaohui Zhang; Zhuan Ge; Teng Man; Sergio Andres Galindo-Torres (Computers and Geotechnics, 2026)

White peroxidase-mimicking Mn-MOF enabled smartphone-assisted colorimetric sensor for on-site visual detection of perfluorooctane sulfonate in water samples - Shao-Hua Wen; Jun Zhan; Hao Wu; Yule Ji; Qingpeng Zhao; Ziqi Yuan; Junping Ma; Sha Yu; Yuanzhen Zhou; Man Ge (Journal of Environmental Chemical Engineering, 2026)

Flood susceptibility prediction in the Indo-China Peninsula using 21 years of inundation occurrence data and machine learning - Gangya Huang; Alex Hay-Man Ng; Qianqian Zhou; Qinggaozi Zhu; Zheyuan Du; Linlin Ge (Journal of Hydrology, 2026)

The F-box protein ZmFBK1 facilitates autophagy-mediated degradation of maize NLR protein Rp1-D21 to suppress the hypersensitive response - Chang-Xiao Tang; Shi-Jun Ma; Qi-Dong Ge; Yang Sun; Tong-Tong Liu; Man Yang; Zi-Xuan Kang; Yu-Chen Dai; Xuan Zhang; Xueman Liu; Yanyong Cao; Guan-Feng Wang (Molecular Plant, 2026)

Highly sensitive colorimetric 3D covalent organic framework sensors with artificial intelligence analysis enabled early detection of plant diseases - Asmaa Gbiliy; Ibrahim Senosy; Marwa A.A. Saadan; Mahmoud Sayed; I.P.W.A.V. Kumara; Ge-Fei Hao; Man-Qun Wang (Chemical Engineering Journal, 2026)

Gender-specific association between PM2.5 exposure and cognitive function in middle-aged and elderly chinese: Evidence from CHARLS - Man Quan; Jing Cui; Yukui Chen; Jiayi Hao; Chenshu Ge; Xiaomei Li; Juan Wang; Duolao Wang; Leilei Pei; Yijun Kang; Lu Ye (Air Quality, Atmosphere & Health, 2026)

Perspectives on the role of postbiotics in meat and meat products: Current status and future trends - Du-xin Jin; Gui-peng Zou; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Meat Science, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Impacts of climate change and land use changes on heat island effect in the Guangdong-Hong Kong-Macao Greater Bay Area under the SSP-RCP framework - Xin Yan; Alex Hay-Man Ng; Xun Liu; Qianqian Zhou; Linlin Ge (Sustainable Cities and Society, 2025)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

Changes in induced-antipredation defense traits and transcriptome regulation of rotifer Brachionus calyciflorus in response to nanoplastics - Huanhuan Xu; Xiaodan Nan; Yingying Ge; Yuxiang Zhou; Chunting Zhou; Kangning Liu; Zhenzhen Li; Man Zhang; Jiaxin Yang (Journal of Oceanology and Limnology, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Experimental and network pharmacology certify itraconazole mitigates fluorouracil-induced intestinal damage by inhibiting mTOR-mediated intestinal senescence - Yuchen Ge; Bingxiang Zhao; Man Li; Zhenglin Li; Shirui Bai; Qishan Zhang; Xue Wang; Guangming Wang; Jianjie Cheng; Xiaobo Wang (Toxicology and Applied Pharmacology, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Carbon emission of rural household in China: A STIRPAT analysis of 30 provinces 2011–2021 - Dandong Ge; Man Huang; Xin Jin; Zhaoyuan Liang; Wen-shao Chang; Xunzhi Yin (Energy and Buildings, 2025)

A new strategy for removing insecticide etoxazole from soil using a combination of a novel Paracoccus versutus Y4 and a fungal mycelium carrier - Man Xu; Xue Luo; Xin-Li Yan; Xiao-Yu Cai; Lin-Lin Wang; Feng Ge; Hong-Wei Wang (Journal of Hazardous Materials, 2025)

Electrochemical degradation of toluene-2,4-diamine by graphene oxide-modified Ti/Sb-SnO2/α-PbO2/β-PbO2 anode: Performance and mechanism - Shuaishuai Man; Jun Zhang; Hebin Bao; Yifan Ge; Youcun Bai; Xinyu Liu; Ziyang Li; Liwei Qiu; Zhenzhen Zhao; Qun Yan (Environmental Research, 2025)

Inhibition of placental 11β-HSD2 expression through cAMP/PKA signaling pathway induces intrauterine growth retardation - Caiyun Ge; Luting Yu; Man Fang; Xinrui Cao; Huijun Chen; Hui Wang (Toxicology Letters, 2025)

Cadmium exposure and health outcomes:An umbrella review of meta-analyses - Wenzhuo Xu; Sainan Wang; Wenhua Ruan; Mingyue Hao; Kele Jiang; Hao Guo; Anyi Geng; Mengting Man; Zheng Hu; Yun Liu; Guifang Jin; Haiyan Shi; et al. (Environmental Research, 2025)

Optimization of surface modification conditions of jute powder and study of its adsorption behavior and mechanism for Pd(II) - Man Lu; Manman Ge; Yong Li; Guozhen Wang; Xinke Kang; Haiyan Wu; Ling Tan; Haigang Dong; Jianping Xie; Bo He (Journal of Environmental Chemical Engineering, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Decadal water management measures moderated the subsidence of North China Plain - Hang Xu; Man Li; Teng Wang; Daqing Ge; Yun Pan (Science Bulletin, 2025)

Synergistic surfactant cleaning-bioaugmentation strategy enables deep remediation of heavily petroleum-contaminated soils: Field validation and microbial mechanism - Zhineng Wu; Linhao Kang; Quanli Man; Yaduo Yang; Jiao Wang; Hongjiang Ge; Xiaodong Ma (International Biodeterioration & Biodegradation, 2025)

Combination of NRPS/PKS tuning and morphological engineering enhanced iturin A production in Bacillus amyloliquefaciens - Zheng-Jie Hou; Hai-Meng Lai; Kai-Ge Song; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng (Chemical Engineering Journal, 2025)

Water-saturated CO2 injection in a carbonate rock – Effect of pore heterogeneity - Hang Yin; Jiachao Ge; Patrick Kin Man Tung; Yamin Wang; Saira; Ahmad Khayyat; Furqan Hussain (Marine and Petroleum Geology, 2025)

Environmentally relevant concentrations of DBDPE (decabromodiphenyl ethane) induce intestinal toxicity in silkworms (Bombyx mori L.) - Xue Luo; Rui Xing; Man Xu; Hui-Jun Jiang; Yu-Rui Wang; Ming-Yue Hu; Hao Zhang; Feng Ge; Wei Zhang; Hong-Wei Wang (Environmental Pollution, 2025)

Drosophila modeling to identify causative genes and reveal the underlying molecular mechanisms for primary ovarian insufficiency - Yanbin Ma; Yuxin Liu; Man Xu; Xinhuan Yin; Chenyu Hu; Xiaohang Yang; Wanzhong Ge (Journal of Molecular Medicine, 2025)

Infiltration characteristics of slurries in porous media based on the coupled Lattice-Boltzmann discrete element method - Xudong Zhang; Tianwen Huang; Zhuan Ge; Teng Man; Herbert E. Huppert (Computers and Geotechnics, 2025)

Sexual differentiation and juvenile hermaphroditism in silver pomfrets: Direction, process, and dietary factors - Yaya Li; Mingzhe Yuan; Peng Shi; Keyan Cai; Jiabao Hu; Man Zhang; Youyi Zhang; Yuanbo Li; Mengke Tang; Zukang Feng; Chunlai Qin; Wei Ge; et al. (Aquaculture, 2024)

Enhancing adsorbent performance for direct air capture of CO2 by in-situ amine-grafting of layered double hydroxides - Bingyao Ge; Chunping Chen; Yifei Xu; Samuel Roberts; Man Zhang; Qingyang Shao; Dermot O’Hare; Xuancan Zhu (Chemical Engineering Journal, 2024)

Exploring Jiangshui-originated probiotic lactic acid bacteria as starter cultures: Functional properties and fermentation performances in pear juice - Du-xin Jin; Yu-xuan Jin; Wei Zhang; Wei Cao; Rui Liu; Man-gang Wu; Qing-feng Ge; Hai Yu (Food Bioscience, 2024)

TNF-α and RPLP0 drive the apoptosis of endothelial cells and increase susceptibility to high-altitude pulmonary edema - Yi-Ling Ge; Pei-Jie Li; Ying-Rui Bu; Bin Zhang; Jin Xu; Si-Yuan He; Qing-Lin Cao; Yun-Gang Bai; Jin Ma; Lin Zhang; Jie Zhou; Man-Jiang Xie (Apoptosis, 2024)
High-altitude pulmonary edema (HAPE) is a fatal threat for sojourners who ascend rapidly without sufficient acclimatization. Acclimatized sojourners and adapted natives are both insensitive to HAPE but have different physiological traits and molecular bases. In this study, based on GSE52209, the gene expression profiles of HAPE patients were compared with those of acclimatized sojourners and adapted natives, with the common and divergent differentially expressed genes (DEGs) and their hub genes identified, respectively. Bioinformatic methodologies for functional enrichment analysis, immune infiltration, diagnostic model construction, competing endogenous RNA (ceRNA) analysis and drug prediction were performed to detect potential biological functions and molecular mechanisms. Next, an array of in vivo experiments in a HAPE rat model and in vitro experiments in HUVECs were conducted to verify the results of the bioinformatic analysis. The enriched pathways of DEGs and immune landscapes for HAPE were significantly different between sojourners and natives, and the common DEGs were enriched mainly in the pathways of development and immunity. Nomograms revealed that the upregulation of TNF-α and downregulation of RPLP0 exhibited high diagnostic efficiency for HAPE in both sojourners and natives, which was further validated in the HAPE rat model. The addition of TNF-α and RPLP0 knockdown activated apoptosis signaling in endothelial cells (ECs) and enhanced endothelial permeability. In conclusion, TNF-α and RPLP0 are shared biomarkers and molecular bases for HAPE susceptibility during the acclimatization/adaptation/maladaptation processes in sojourners and natives, inspiring new ideas for predicting and treating HAPE.

Research on Precise Feeding Strategies for Large-Scale Marine Aquafarms - Yizhi Wang; Yusen Zhang; Fengyuan Ma; Xiaomin Tian; Shanshan Ge; Chaoyuan Man; Maohua Xiao (Journal of Marine Science and Engineering, 2024)
Breeding in large-scale marine aquafarms faces many challenges in terms of precise feeding, including real-time decisions as to the precise feeding amount, along with disturbances caused by the feeding speed and the moving speed of feeding equipment. Involving many spatiotemporal distributed parameters and variables, an effective predictive model for environment and growth stage perception is yet to obtained, further preventing the development of precise feeding strategies and feeding equipment. Therefore, in this paper, a hierarchical type-2 fuzzy system based on a quasi-Gaussian membership function for fast, precise, on-site feeding decisions is proposed and validated. The designed system consists of two layers of decision subsystems, taking in different sources of data and expert experience in feeding but avoiding the rule explosion issue. Meanwhile, the water quality evaluation is considered as the secondary membership function for type-2 fuzzy sets and used to adjust the parameters of the quasi-Gaussian membership function, decreasing the calculation load in type reduction. The proposed system is validated, and the results indicate that the shape of the primary fuzzy sets is altered with the secondary membership, which influences the defuzzification results accordingly. Meanwhile, the hardware of feeding bins for UAVs with variable-speed coupling control systems with disturbance compensation is improved and validated. The results indicate that the feeding speed can follow the disturbance in the level flying speed.

Monitoring slope stabilization of a reactivated landslide in the Three Gorges Reservoir Region (China) with multi-source satellite SAR and optical datasets - Jianming Kuang; Linlin Ge; Alex Hay-Man Ng; Stuart R. Clark; Sadra Karimzadeh; Masashi Matsuoka; Zheyuan Du; Qi Zhang (Landslides, 2024)

Hydrogen-bond tuned conjugated architectures for nitric oxide sensing in single-benzene framework: Advances and mechanistic insights - Feng-Zao Chen; Cun-Bin Du; Yi-Chao Wang; Jie Zhu; Ge Cheng; Kai-Bin Li; De-Man Han; Xiao-Yu Wu (Analytica Chimica Acta, 2024)

First retrieval of daily 160 m aerosol optical depth over urban areas using Gaofen-1/6 synergistic observations: Algorithm development and validation - Jiadan Dong; Tianhao Zhang; Lunche Wang; Zhengqiang Li; Man Sing Wong; Muhammad Bilal; Zhongmin Zhu; Feiyue Mao; Xinghui Xia; Ge Han; Qiangqiang Xu; Yu Gu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Design of bifunctional ultrathin MnO2 nanofilm with laccase-like activity for sensing environmental pollutants containing phenol groups - Sheng-Tao Wu; Hui-Qi Su; Qian-Xiang Xiao; Zhi-Yu Qiu; Gang-Qiang Huang; Man-Ni He; Yi Ge; Cong-Hui Wang; Ying-Wu Lin (Journal of Hazardous Materials, 2024)

Facile synthesis of bead-chain structured MWCNTs@CeO2 with oxygen vacancies-rich for promoting electrochemical energy storage - Xiao-Man Cao; Jia-Qi Chen; Xin-Rui Zhao; Hao Ge; Daliang Liu; Qiong Wu; Zhi-Jia Sun; Qingguo Zhang (Chemical Engineering Journal, 2024)

A novel framework for combining polarimetric Sentinel-1 InSAR time series in subsidence monitoring - A case study of Sydney - Alex Hay-Man Ng; Ziyue Liu; Zheyuan Du; Hengwei Huang; Hua Wang; Linlin Ge (Remote Sensing of Environment, 2023)

Integrative transcriptome and metabolome revealed the molecular mechanism of Bacillus megaterium BT22-mediated growth promotion in Arabidopsis thaliana - Xiao Liu; Yan Du; Xiaofan Na; Man Wang; Ying Qu; Linghui Ge; Yuanmeng Wang; Linqi Gao; Wenke Bai; Yurong Bi; Libin Zhou (Journal of Plant Physiology, 2023)

Porous carbon nanofibers supported Zn@MnO sorbents with high dispersion and loading content for hot coal gas desulfurization - Yu Feng; Man Zhang; Yangjie Sun; Chunyan Cao; Jiancheng Wang; Mingzheng Ge; Weilong Cai; Jie Mi; Yuekun Lai (Chemical Engineering Journal, 2023)

Exploring the role of protein DJ-1 in quality of pale, soft and exudative (PSE) and red, firm and non-exudative (RFN) pork during post-mortem aging - Rui Liu; Keyue Li; Tianyi Yang; Lun Yang; Man Qin; Hai Yu; Mangang Wu; Qingfeng Ge; Wenbin Bao; Shenglong Wu (Food Chemistry, 2023)

PM2.5-related DNA methylation and the association with lung function in non-smokers - Ge Mu; Xiuquan Nie; Shijie Yang; Zi Ye; Man Cheng; Lieyang Fan; Weihong Qiu; Qiyou Tan; Min Zhou; Yanjun Guo; Weihong Chen (Environmental Pollution, 2023)

OsAPL controls the nutrient transport systems in the leaf of rice (Oryza sativa L.) - Zhen Yan; Man-Yu Yang; Biligen-Gaowa Zhao; Guo Li; Qing Chao; Feng Tian; Ge Gao; Bai-Chen Wang (Planta, 2022)

Variational Quality Control of Non-Gaussian Innovations in the GRAPES m3DVAR System: Mass Field Evaluation of Assimilation Experiments - Jie He; Xulin Ma; Xuyang Ge; Juanjuan Liu; Wei Cheng; Man-Yau Chan; Ziniu Xiao (Advances in Atmospheric Sciences, 2021)

Selection of reliable reference genes for analysis of gene expression in the rat placenta - Caiyun Ge; Pengxia Yu; Man Fang; Hui Wang; Yuanzhen Zhang (Molecular and Cellular Biochemistry, 2021)

Towards a revised framework of modified time series InSAR for mapping land deformation - Zheyuan Du; Linlin Ge; Alex Hay-Man Ng; Qi Zhang (Journal of Geodesy, 2020)

α-Mangostin suppresses NLRP3 inflammasome activation via promoting autophagy in LPS-stimulated murine macrophages and protects against CLP-induced sepsis in mice - Yun Ge; Xin Xu; Qiqiang Liang; Yongshan Xu; Man Huang (Inflammation Research, 2019)

Coseismic deformation and source model of the 12 November 2017 M W 7.3 Kermanshah Earthquake (Iran–Iraq border) investigated through DInSAR measurements - Jianming Kuang; Linlin Ge; Graciela Isabel Metternicht; Alex Hay-Man Ng; Hua Wang; Mehdi Zare; Farnaz Kamranzad (International Journal of Remote Sensing, 2019)

Investigation on mining subsidence over Appin–West Cliff Colliery using time-series SAR interferometry - Zheyuan Du; Linlin Ge; Alex Hay-Man Ng; Xiaojing Li (International Journal of Remote Sensing, 2018)

Characteristics of polycyclic aromatic hydrocarbons in PM2.5 emitted from different cooking activities in China - Yun-Chun Li; Jia-Qian Qiu; Man Shu; Steven Sai Hang Ho; Jun-Ji Cao; Ge-Hui Wang; Xian-Xiang Wang; Xiao-Qing Zhao (Environmental Science and Pollution Research, 2018)

Integrated space geodesy for mapping land deformation over Choushui River Fluvial Plain, Taiwan - Linlin Ge; Alex Hay-Man Ng; Zheyuan Du; Horng-Yue Chen; Xiaojing Li (International Journal of Remote Sensing, 2017)

Hydrotubation Combined with Chinese Herbal Medicine for Salpingitic Infecundity: A Systematic Review and Meta-Analysis - Huanhuan Wen; Jinrong Fu; Hong Tang; Man Ge; Linna Feng (Cell Biochemistry and Biophysics, 2015)

Complete nucleotide sequence and gene rearrangement of the mitochondrial genome of Occidozyga martensii - EN LI; XIAOQIANG LI; XIAOBING WU; GE FENG; MAN ZHANG; HAITAO SHI; LIJUN WANG; JIANPING JIANG (Journal of Genetics, 2014)

Sex Differences in Iron Status and Hepcidin Expression in Rats - Wei-Na Kong; Qiao-Man Niu; Lan Ge; Nan Zhang; Shao-Feng Yan; Wei-Bin Chen; Yan-Zhong Chang; Shu-E Zhao (Biological Trace Element Research, 2014)

A robust regression-based linear model adjustment method for SAR interferogram stacking techniques - Kui Zhang; Linlin Ge; Xiaojing Li; Alex Hay-Man Ng (International Journal of Remote Sensing, 2013)

Monitoring ground surface deformation over the North China Plain using coherent ALOS PALSAR differential interferograms - Kui Zhang; Linlin Ge; Xiaojing Li; Alex Hay-Man Ng (Journal of Geodesy, 2013)

Monitoring ground deformation in Beijing, China with persistent scatterer SAR interferometry - Alex Hay-Man Ng; Linlin Ge; Xiaojing Li; Kui Zhang (Journal of Geodesy, 2012)

Deformation mapping in three dimensions for underground mining using InSAR – Southern highland coalfield in New South Wales, Australia - Alex Hay-Man Ng; Linlin Ge; Kui Zhang; Hsing-Chung Chang; Xiaojing Li; Chris Rizos; Makoto Omura (International Journal of Remote Sensing, 2011)

Major Pollutants in Soils of Abandoned Agricultural Land Contaminated by e-Waste Activities in Hong Kong - Brenda Natalia Lopez; Yu Bon Man; Yin Ge Zhao; Jin Shu Zheng; Anna Oi Wah Leung; Jun Yao; Ming Hung Wong (Archives of Environmental Contamination and Toxicology, 2011)

Phenylpropanoid and flavonoids from osteoprotective fraction of Drynaria fortunei - Xin-Luan Wang; Nai-Li Wang; Hao Gao; Ge Zhang; Ling Qin; Man-Sau Wong; Xin-Sheng Yao (Natural Product Research, 2010)

Multi-path PALSAR interferometric observations of the 2008 magnitude 8.0 Wenchuan Earthquake - Kui Zhang; Alex Hay-Man Ng; Linlin Ge; Yusen Dong; Chris Rizos (International Journal of Remote Sensing, 2010)

Mitochondrial Uncoupling Protein-2 (UCP2) Mediates Leptin Protection Against MPP+ Toxicity in Neuronal Cells - Philip Wing-Lok Ho; Hui-Fang Liu; Jessica Wing-Man Ho; Wei-Yi Zhang; Andrew Chi-Yuen Chu; Ken Hon-Hung Kwok; Xuan Ge; Koon-Ho Chan; David Boyer Ramsden; Shu-Leong Ho (Neurotoxicity Research, 2010)

Induction and origin of adventitious shoots from chimeras of Brassica juncea and Brassica oleracea - Xue-Yun Zhu; Man Zhao; Sheng Ma; Ya-Ming Ge; Ming-Fang Zhang; Li-Ping Chen (Plant Cell Reports, 2007)

Construction and characterization of a bacterial artificial chromosome library of marine macroalgaPorphyra yezoensis (Rhodophyta) - Dai Yong Deng; Ge Zhao; Jin Song Xuan; Ji Liang Yang; Lin De Duan; Man Li Weng; Bin Wang (Plant Molecular Biology Reporter, 2004)

Effects of organic solvents on membrane ofTaxus cuspidata cells in - Qiu-man Xu; Jing-sheng Cheng; Zhi-qiang Ge; Ying-jin Yuan (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Activin stimulates goldfish FSH biosynthesis by enhancing FSHβ promoter activity - Wei Ge; Nga-Ling Ko; Flora Yee-Man Pang; Me-Fong Chung; Sze-Wah Lin; Chi-Wai Yuen; Man-Tat Lau; Lin Liu; Young Chang Sohn; Makito Kobayashi; Katsumi Aida (Fish Physiology and Biochemistry, 2003)